Cucurbitacin E reduces obesity and related metabolic dysfunction in mice by targeting JAK-STAT5 signaling pathway - Murtaza, Munazza; Khan, Gulnaz; Aftab, Meha Fatima; Afridi, Shabbir Khan; Ghaffar, Safina; Ahmed, Ayaz; Hafizur, Rahman M.; Waraich, Rizwana Sanaullah (PLOS ONE, 2017)
Several members of cucurbitaceae family have been reported to regulate growth of cancer by interfering with STAT3 signaling. In the present study, we investigated the unique role and molecular mechanism of cucurbitacins (Cucs) in reducing symptoms of metabolic syndrome in mice. Cucurbitacin E (CuE) was found to reduce adipogenesis in murine adipocytes. CuE treatment diminished hypertrophy of adipocytes, visceral obesity and lipogenesis gene expression in diet induced mice model of metabolic syndrome (MetS). CuE also ameliorated adipose tissue dysfunction by reducing hyperleptinemia and TNF-alpha levels and enhancing hypoadiponectinemia. Results show that CuE mediated these effects by attenuating Jenus kinase- Signal transducer and activator of transcription 5 (JAK- STAT5) signaling in visceral fat tissue. As a result, CuE treatment also reduced PPAR gamma expression. Glucose uptake enhanced in adipocytes after stimulation with CuE and insulin resistance diminished in mice treated with CuE, as reflected by reduced glucose intolerance and glucose stimulated insulin secretion. CuE restored insulin sensitivity indirectly by inhibiting JAK phosphorylation and improving AMPK activity. Consequently, insulin signaling was up-regulated in mice muscle. As CuE positively regulated adipose tissue function and suppressed visceral obesity, dyslipedemia, hyperglycemia and insulin resistance in mice model of MetS, we suggest that CuE can be used as novel approach to treat metabolic diseases.